Analysis of Plant Diversity in More Degraded and Less Degraded Forest of Hastinapur in North West Uttar Pradesh - Sharma, Poonam (Indian Forester, 2018)
Different phytosociological attributes of woody vegetation were analyzed along a disturbance gradient in tropical dry deciduous forest of Hastinapur along the three sites. The disturbed site were surveyed for floristic composition, similarity index, concentration of dominance, species diversity, Ã¢diversity at each stratum of woody vegetation. Maximum numbers of trees were recorded from undisturbed site (Site-3). Acacia nilotica, Tectonagrandis (tree species) were present on all the sites although in undisturbed site these species were less in number. Acacia nilotica was dominant species of Highly disturbed (Site-1) and Moderately disturbed (Site-2) sites, whereas on undisturbed site (Site-3) Acacia catechu and Tectonagrandis were the dominant species. Maximum similarity was observed between site-2 and site-3 (69.2%) and minimum between Site-1 and site-2 (25%). The value of CD and H’ for trees were 0.01 on Site-2 to 0.035 on site-1 and 0.oo on site-3 to 0.014 on Site-1 respectively.